O olhar infantil: como crianças de duas escolas natalenses percebem as mudanças climáticas globais - Farias, Alexandra Cavalcante de (2017)
Global Climate Changes (GCC) are generally disclosed and discussed as Global Warming (GW), a term that restricts the problem to an increase in temperature. Besides being just an increase in global temperature, GCC now reaches the public policies sphere, causing interference in the lives of human beings. It is important to point out that in the case of GCC there is a temporal detachment from the current moment to the most alarming consequences of the phenomenon, as well as uncertainty about the effectiveness of mitigation actions, which have their necessarily present long-term answers. It is therefore of utmost importance, consideration of the future, to think not only in behavior changes reflecting today, but in decades and centuries ahead. Taking into account that today's children will experience the most serious consequences of the problem sometime in the future, the study aimed to investigate how 46 children aged 7 a 10 years old from two private schools from Natal perceive GCC through the information they receive about this topic. The study adopted a multi-methodological perspective with the participating children, involving combined techniques of semi-structured interview, drawing and focus group, in order to provide a ludic approach appropriate to this audience. The analysis of the data integrated the results of the three techniques, whose content allowed the creation of thematic axes, related to the theoretical references of the environmental psychology literature. The thematic axes thus obtained were: local-global, cause-consequence, impact on human life – on ecosystems and mitigation - adaptation. The results showed that despite the high complexity, the participants were able to express themselves about the theme, especially when the topics had been previously treated in the school context. This finding, together with the commitment expressed by children with mitigation measures, provides important subsidies for the planning of environmental education projects for this public.